Sociedade, cognição e discurso: desvendando Cora Coralina - Dias, Paula Pinho (2008)
This thesis was developed in accordance with the socio-cognitive line of Critical Discourse Analysis and deals with the forms of biographical representation of poet Cora Coralina constructed by she herself and by other authors. The general objective of this thesis is to contribute to analytical studies of texts written by Brazilian regional authors. The specific objectives are: 1) to examine the poet's biography based on a base text and selected intertexts of her poetic works; 2) to analyze the linguistic expressions of intertexts selected from studies of other authors; and 3) to clip other intertexts of authors whose evaluative representations aid in historically reconstructing the context of Cora Coralina's production of her poetry. Based on the assumption of dialectics between the social and the individual, one recognizes that Cora Coralina's poetry is guided by cultural values of the social memory of the groups with which she lived in Glose proximity, in or out of the city of Goiás, and the theoretic-analytical procedure adopted was the interrelation among the society, cognition, and discourse categories. Findings of the analysis indicated that: 1) although the social guides her individual, there is opposition between traditional cultural values and those represented by Cora Coralina; 2) two social groups stand out in Goiás - the conservative and the innovative - which proves the dynamics of the culture in each contemporaneity; 3) the poet's lexical choices are guided by what she experienced within her social group; 4) the evaluative representations' of her autobiography confront the past and the contemporaneity of her poetic produefion and focus personal experiences of privations which, by means of passionate modalizations, ramify into lack and neediness